Amphiphilic thickener for personal care

A crosslinked polymer thickener with a silicone shell addresses the challenge of maintaining long-lasting makeup and UV protection in personal care products by enhancing moisture feel and reducing stickiness and color transfer, achieved through spherical particle formation and polymerization methods.

JP2025010098APending Publication Date: 2025-01-20LG HOUSEHOLD & HEALTH CARE LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024107412
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-11-28
Filing Date
2024-07-03
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing personal care compositions, such as cosmetics and sunscreens, face challenges in maintaining long-lasting makeup and UV protection while reducing stickiness and color transfer, often compromising moisture feel due to water-in-oil formulations that enhance durability but feel dry and increase stickiness.

Method used

A crosslinked polymer thickener is developed using a water-soluble monomer and a silicone-containing monomer, formed into spherical particles with a silicone polymer shell, enhancing moisture retention and reducing stickiness through PIT or precipitation polymerization methods.

Benefits of technology

The amphiphilic thickener maintains particle shape and viscosity, providing improved moisture feel, reduced stickiness, and enhanced UV protection durability by suppressing moisture evaporation and improving sebum resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010098000021
    Figure 2025010098000021
  • Figure 2025010098000022
    Figure 2025010098000022
  • Figure 2025010098000023
    Figure 2025010098000023
Patent Text Reader

Abstract

To provide a thickener that may be used in cosmetics and the like, and more specifically, to provide a thickener that may provide moisture with less stickiness.SOLUTION: In the present invention, a thickener in the form of homogeneous fine particles whose surface is coated with a silicone polymer may be prepared using phase inversion temperature (PIT) polymerization while allowing the polymerization reaction to proceed in a uniform reverse phase emulsion with a small particle size. In addition, the thickener may be prepared using precipitation polymerization. In addition, the spherical particle-shaped thickener prepared by the present invention has the advantage of high moisture retention due to the coated silicone polymer, which is the shell, while maintaining the shape of the particle even when swelling in moisture, and the spherical particles whose surface is coated with the silicone polymer have high dispersibility in an oil phase, which helps to maintain makeup, and the spherical polymer has the effect of reducing stickiness and staining.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thickener that can be used in personal care compositions and products such as cosmetics, and more particularly to a thickener that is less sticky and can impart a moist feel. [Background technology]

[0002] An important attribute when using makeup or sunscreen products is high makeup durability or UV protection durability, and the makeup effect lasts for a long time even after one application without touching up or reapplication. However, in order to increase makeup durability, water-in-oil (W / O) formulations that have excellent resistance to water from sweat and sebum from sebum are used, but this has the disadvantage of reducing the sense of moisture and making the product feel dry. Furthermore, the volatile oils used for quick setting when applied to the skin reduce the moldability of the formulation during product manufacturing, which can also cause productivity to decrease.

[0003] If the aqueous phase ratio of the formulation is increased to solve this problem, the stability of the formulation is hindered and phase separation occurs easily due to the characteristics of the water-in-oil type, and if an emulsifier is used to strengthen the stability of the formulation, stickiness increases, creating a vicious cycle.In addition, if a film former is used to improve the durability of the makeup, stickiness and color transfer also increase.

[0004] Therefore, there is a need for a technology that can improve the durability of makeup and UV protection while also increasing the sense of moisture and reducing stickiness and color transfer.

[0005] To solve this problem, the inventors have discovered that based on the fine particle structure polymer of the previous research, Patent Registration No. 10-2531603, the core part is made of a polymer that can absorb water and maintain viscosity, and the shell part is chemically coated with a silicone polymer to suppress the evaporation of water from the core part, thereby increasing the sense of moisture, and the silicone polymer in the shell part improves makeup durability, stickiness, and color transfer, thereby completing the present invention. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Republic of Korea Patent No. 10-2531603 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide an amphiphilic thickener for personal care that can enhance moisture sensation and reduce stickiness and color transfer.

[0008] It is still another object of the present invention to provide a cosmetic composition which contains the amphiphilic thickener of the present invention and has excellent cosmetic durability and UV protection durability. [Means for solving the problem]

[0009] In order to achieve the above object, the amphiphilic thickener of the present invention comprises a crosslinked polymer obtained by polymerization reaction of a water-soluble monomer represented by the following chemical formula 1, a crosslinkable monomer, and a silicone-containing monomer represented by the following chemical formula 2.

[0010] [Chemical formula 1] [ka]

[0011] In the above Chemical Formula 1, R1 is -H, -CH3, -CH2CH3 or -(CH2) m CH3, where m=1-3; R2 is -OX, NH2 or -NH-R3-SO3Y; R3 is -(CH2)-, -(CH2)2-, -(CH2)3-, -(CH2)4-, -(CH2)2(CH3)2- or -(CH2)3CH3-; X and Y are H + , Na + , Li + , K + or NH3 + where X and Y may be the same as each other.

[0012] [Chemical formula 2] [ka]

[0013] In the above Chemical Formula 2, m is an integer from 1 to 5; n is an integer from 10 to 5000, R1 is hydrogen or C 1-3 is an alkyl group, R2 is a hydroxy group, C 1-3 It is an alkyl group or a vinyl group.

[0014] In one embodiment, the present invention includes a method for preparing the amphiphilic thickener, comprising dissolving and heating the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2, and then adding a reaction initiator to polymerize the mixture to prepare a crosslinked polymer.

[0015] In one embodiment, the method for producing the amphiphilic thickener of the present invention may include the steps of producing an oil-in-water emulsion composition including an aqueous phase containing a water-soluble monomer represented by the chemical formula 1 and a crosslinkable monomer, and an oil phase containing a silicone-containing monomer represented by the chemical formula 2 and a non-polar organic solvent, heating to 60°C or higher to produce a water-in-oil reverse emulsion composition, and adding a reaction initiator to carry out a polymerization reaction to produce a crosslinked polymer.

[0016] In one embodiment, the amphiphilic thickener may be prepared using a phase inversion temperature (PIT) polymerization method.

[0017] In yet another embodiment, the method for producing the amphiphilic thickener of the present invention may include the steps of dissolving the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2 in an alcohol-based solvent, heating the mixture to 60° C. or higher, and adding a reaction initiator to carry out a polymerization reaction to produce a crosslinked polymer. A precipitation polymerization method may be used as the method for producing the amphiphilic thickener.

[0018] In one embodiment, the method for preparing the amphiphilic thickener may further comprise obtaining the thickener in solid form, for example using a solvent-free precipitation method of the crosslinked polymer. Effect of the Invention

[0019] The present invention provides a homogeneous particulate thickener whose core is composed of a water-soluble polymer crosslinker and whose surface is coated with a silicone polymer. Therefore, the spherical particulate thickener of the present invention has the advantage that it maintains its particle shape even when swollen from the aqueous phase, and its moisture retention is enhanced by the silicone polymer coating, which is the shell part. In addition, the spherical particles whose surface is coated with a silicone polymer have a high dispersing power in the oil phase, which helps to maintain the makeup's durability, and the spherical polymer also has the effect of reducing stickiness and color transfer. [Brief description of the drawings]

[0020] [Figure 1] FIG. 2 is an illustrative diagram showing a method for producing an amphiphilic thickener by inverse emulsion polymerization in the present invention. [Diagram 2] FIG. 2 is an illustrative diagram showing a method for producing an amphiphilic thickener by precipitation polymerization in the present invention. [Diagram 3] 1 is a graph showing the results of confirming the water retention of an amphiphilic thickener according to the present invention. [Figure 4] 1 is a photograph showing the results of checking color transfer of a makeup formulation to which an amphiphilic thickener according to the present invention is applied. [Diagram 5] 1 is a graph showing the stickiness of a sun cream formulation using an amphiphilic thickener according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] However, the present invention can be modified in various ways and can have various forms, and the specific examples and explanations described below are intended to aid in the understanding of the present invention and are not intended to limit the present invention to the specific disclosed forms. The scope of the present invention should be understood to include all modifications, equivalents, or alternatives that fall within the spirit and technical scope of the present invention.

[0022] The present invention will now be described in more detail.

[0023] In the present invention, the term "thickener" refers to the crosslinked polymer produced by the production method of the present invention, and refers to a solution in which the crosslinked polymer is dispersed. In particular, the thickener refers to a substance that is usually used for the purpose of increasing the viscosity of a personal care composition or a personal care product.

[0024] In one embodiment, the amphiphilic thickener of the present invention comprises a crosslinked polymer obtained by polymerization of a water-soluble monomer and a crosslinkable monomer represented by the following chemical formula 1 and a silicone-containing monomer represented by the following chemical formula 2:

[0025] In one embodiment, the water-soluble monomer may be a compound represented by the following formula 1:

[0026] [ka]

[0027] In the above Chemical Formula 1, R1 is -H, -CH3, -CH2CH3 or -(CH2) m CH3, where m=1-3; R2 is -OX, NH2 or -NH-R3-SO3Y; R3 is -(CH2)-, -(CH2)2-, -(CH2)3-, -(CH2)4-, -(CH2)2(CH3)2- or -(CH2)3CH3-; X and Y are H + , Na + , Li + , K + or NH3 + where X and Y may be the same as each other.

[0028] [Chemical formula 2] [ka]

[0029] In the above Chemical Formula 2, m is an integer from 1 to 5; n is an integer from 10 to 5000, R1 is hydrogen or C 1-3 is an alkyl group, R2 is a hydroxy group, C 1-3 It is an alkyl group or a vinyl group.

[0030] In one embodiment, the method for preparing the amphiphilic thickener of the present invention may include a step of preparing an oil-in-water emulsion composition (step 1-1) including an aqueous phase including a water-soluble monomer represented by the above formula 1 and a crosslinkable monomer, and an oil phase including a silicone-containing monomer represented by the above formula 2 and a non-polar organic solvent, a step of preparing a water-in-oil reverse phase emulsion composition by heating to 60° C. or higher (step 1-2), and a step of adding a reaction initiator to carry out a polymerization reaction to prepare a crosslinked polymer (step 1-3).

[0031] In one embodiment, the amphiphilic thickener may be prepared by using a phase inversion temperature (PIT) polymerization method. In the PIT polymerization method, an oil-in-water emulsion composition may be formed at a low temperature in step 1-1, and then the temperature may be increased in step 1-2 to convert the composition into a water-in-oil inverse emulsion composition.

[0032] In the present invention, step 1-1 is a step of preparing an oil-in-water emulsion composition including an aqueous phase containing a water-soluble monomer represented by Chemical Formula 1 and a crosslinkable monomer, and an oil phase containing a silicone-containing monomer represented by Chemical Formula 2 and a non-polar organic solvent.

[0033] In the present invention, the aqueous phase in step 1-1 includes the water-soluble monomer represented by Formula 1 and the crosslinkable monomer.

[0034] In one embodiment, the water-soluble monomer represented by Chemical Formula 1 in step 1-1 may be at least one selected from the group consisting of acrylamidomethylpropanesulfonic acid (AMPS), acrylic acid, acrylamide, and polyethylene glycol acrylate.

[0035] Specifically, the water-soluble monomer represented by the above Chemical Formula 1 may be a compound represented by the following Chemical Formula 1a:

[0036] [Chemical formula 1a] [ka]

[0037] In the present invention, the content of the water-soluble monomer represented by Chemical Formula 1 in step 1-1 is not particularly limited, but may be, for example, 10 to 99 wt%, preferably 30 to 95 wt%, and more preferably 50 to 95 wt%, based on 100 wt%, which is the total of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2. Within this range, the stability of the composition is more stable, and the stickiness improving effect is more excellent.

[0038] In one embodiment, the crosslinkable monomer in step 1-1 may be a compound having two or more acrylate groups, two or more acrylamide groups, or two or more vinyl groups. As such a crosslinkable monomer, for example, one or more selected from the group consisting of trimethylolpropane ethoxylate triacrylate (TMPETA), trimethylolpropane triacrylate (TMPTA), methylenebisacrylamide, divinylsulfone, divinylbenzene, divinyl ether, divinylacetylene, polyglycol diacrylate, polyglycol triacrylate, and 4-arm-polyglycol tetraacrylate may be used.

[0039] In one embodiment, the crosslinkable monomer in step 1-1 may more preferably be trimethylolpropane ethoxylate triacrylate (TMPETA), trimethylolpropane triacrylate (TMPTA), or a combination thereof. The crosslinkable monomer is a compound having three or more crosslinking points, which can increase the molecular weight of the crosslinked product, thereby increasing the viscosity.

[0040] In the present invention, the content of the crosslinking monomer in step 1-1 is not particularly limited, but for example, the content of the crosslinking monomer may be 0.01 to 20 wt%, preferably 0.1 to 10 wt%, and more preferably 0.5 to 5.0 wt%, based on 100 wt%, which is the total weight of the water-soluble monomer represented by Chemical Formula 1, the crosslinking monomer, and the monomer including silicone represented by Chemical Formula 2. Within this range, the stability of the composition is better, or the stickiness improving effect is better.

[0041] In one embodiment, the solvent of the aqueous phase in step 1-1 may be water (distilled water).

[0042] In one embodiment, the pH of the aqueous phase in step 1-1 is not particularly limited, and may be, for example, 5 to 9. The pH may be adjusted using a conventional pH adjuster, for example, ammonia water.

[0043] In the present invention, the oil phase in step 1-1 may include a silicone-containing monomer represented by Formula 2 and an organic solvent.

[0044] In the present invention, the content of the silicone-containing monomer represented by Chemical Formula 2 in step 1-1 is not particularly limited, but may be, for example, 1 to 70 wt%, preferably 5 to 60 wt%, and more preferably 10 to 50 wt%, based on 100 wt%, which is the total of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2. Within this range, the stability of the composition is better, or the stickiness improving effect is better.

[0045] In one embodiment, the organic solvent may be a non-polar organic solvent, specifically, 6-17 It may be a hydrocarbon oil, 6-17 If the carbon number is outside the above range, the production efficiency in the polymerization reaction may decrease.

[0046] In one embodiment, heptane may be used as the non-polar organic solvent. Heptane has a boiling point of 98°C, and is not restricted in the polymerization process according to the present invention compared to other organic solvents. During the process, heat may be generated due to an explosive reaction during the initiator introduction process, and the temperature inside the reactor may rise by about 5 to 10°C. The method of slowly introducing the initiator to maintain the reaction temperature constant has the disadvantage of increasing the process time when applied to a mass production process, which increases the production cost. In addition, if the reaction is heated above the boiling point, the reactants may bump and the reactor may explode, so management of the reaction heat is a very important factor in mass production. Therefore, in the present invention, by using heptane as the organic solvent, the thickener of the present invention can be easily produced without process restrictions.

[0047] In the present invention, the oil phase in step 1-1 may further include a surfactant.

[0048] In one embodiment, one or more surfactants may be used as the surfactant in step 1-1. The total HLB value of the surfactants may be 6 to 14, 7 to 10, or 8 to 9. In this case, the total HLB value means the HLB value of one surfactant when one surfactant is used, and means the sum of the HLB values ​​of two or more surfactants when two or more surfactants are used. When the total HLB value is 6 or less, the surfactant is strongly hydrophobic and exists as a water-in-oil type reverse phase emulsion at room temperature, and is polymerized without a phase inversion process, so that the effect of reducing the size of the emulsion may be insufficient. In addition, when the total HLB value is 14 or more, the surfactant is strongly hydrophilic and maintains an oil-in-water type emulsion in which the outer phase is a water phase, and spherical particles are not formed, so that the amorphous state of the thickener produced may increase.

[0049] In one embodiment, two types of surfactants may be used as the surfactant in step 1-1. In this case, a surfactant having an HLB value of 3 to 8 may be used in combination with a surfactant having an HLB value of 8 to 16, or a surfactant having an HLB value of 5 to 7 may be used in combination with a surfactant having an HLB value of 9 to 11.

[0050] In one embodiment, polyoxyethylene (3) oleyl ether (HLB=6.6) and polyoxyethylene (6) oleyl ether (HLB=9.6) may be used in combination as the surfactant in step 1-1. Specifically, polyoxyethylene (3) oleyl ether (HLB=6.6) and polyoxyethylene (6) oleyl ether (HLB=9.6) may be used in combination in a weight ratio of 1:1, and in this case, the HLB value may be 8.1.

[0051] Specifically, by appropriately combining a surfactant with an HLB value of 3-8 and two surfactants with an HLB value of 8-16, or a surfactant with an HLB value of 5-7 and two surfactants with an HLB value of 9-11, the polymerization reaction can be carried out in a uniform inverse emulsion phase with small particle size using a PIT (phase inversion temperature) polymerization method in which an oil-in-water (o / w) emulsion phase at room temperature is converted to a water-in-oil (w / o) emulsion phase at a certain temperature or higher. As a result, the present invention can produce a thickener in the form of uniform spherical particles.

[0052] The thickener in the form of spherical microparticles polymerized by the above method has the advantages of not only maintaining the particle shape even when swollen in an aqueous phase, but also having a transparent appearance and high stability due to the uniform particle dispersion.

[0053] In one embodiment, the content of the surfactant in step 1-1 is not particularly limited, but may vary depending on the type of organic solvent. Specifically, the content of the surfactant may be 5 to 30% by weight based on 100% by weight of the total of purified water, organic solvent, surfactant, water-soluble monomer represented by Chemical Formula 1, crosslinkable monomer, and silicone-containing monomer represented by Chemical Formula 2. Within this content range, phase inversion of the emulsion may be possible, and PIT polymerization may be easily performed.

[0054] In one embodiment, the weight ratio of the aqueous phase to the oil phase in step 1-1 may be 30:70 to 70:30. Within this range, the composition is more stable or the stickiness improving effect is more excellent.

[0055] In the present invention, the step 1-2 is a step of preparing a water-in-oil type reverse emulsion composition by heating to 60° C. or more. The heating in the step 1-2 may be performed at 50° C. to 80° C., preferably 55° C. to 75° C. If the temperature is lower than 50° C., there is a problem that the phase transition phenomenon of the emulsion is difficult to occur.

[0056] In one embodiment, the emulsion prepared in step 1-1 of the present invention has an oil-in-water type at room temperature, and may be inverted to a water-in-oil type emulsion by step 1-2. The emulsion produced by the phase inversion may have the effect of reducing the size of the emulsion, and may have the effect of reducing the particle size of the polymer prepared in the following step.

[0057] In one embodiment, the reaction temperature in step 1-2 may be, for example, 62° C. or higher, 65° C. or higher, 70° C. or higher, or 75° C., and the upper limit may be 100° C. Within this temperature range, the thickener may be produced more stably.

[0058] In the present invention, steps 1 to 3 are steps of adding a reaction initiator to carry out a polymerization reaction to prepare a crosslinked polymer.

[0059] In one embodiment, the type of reaction initiator in steps 1 to 3 is not particularly limited to a general radical polymerization initiator, and may be selected from the group consisting of peroxides and azo compounds. The peroxide initiator may be benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, cumyl hydroperoxide, hydrogen peroxide, or potassium persulfate, and the azo compound initiator may be azo nitrile, azo ester, azo amide, azo imidazolin, azo amidine, macro azo initiator, etc. In the present invention, it is preferable to use an azo compound initiator, more preferably 4,4'-Azobis(4-cyanovaleric acid), because it is advantageous in terms of polymerization reaction efficiency.

[0060] In the present invention, after preparing an inverse emulsion, an initiator is added and reacted to obtain a crosslinked polymer having the viscosity desired in the present invention, i.e., a thickener, and the yield of the thickener can be increased.

[0061] In one embodiment, the reaction temperature in steps 1 to 3 may be 62° C. or higher, 65° C. or higher, 70° C. or higher, or 75° C., with the upper limit being 100° C. Within this temperature range, the thickener may be produced more stably.

[0062] In one embodiment, the steps 1 to 3 may be carried out for a reaction time of 1 to 12 hours, preferably 2 to 6 hours.

[0063] In yet another embodiment of the present invention, the method for producing the amphiphilic thickener of the present invention includes the steps of dissolving the water-soluble monomer represented by the Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by the Chemical Formula 2 in an alcohol-based solvent (Step 2-1); A stage of heating to 60°C or higher (stage 2-2), and A step (step 2-3) of adding a reaction initiator to carry out a polymerization reaction to produce a cross-linked polymer may also be included.

[0064] In one embodiment, the amphiphilic thickener may be prepared by polymerization using a precipitation polymerization method. The water-soluble monomer of formula 1, the silicone-containing monomer of formula 2, the crosslinking monomer, and the reaction initiator used in the precipitation polymerization method may be the same as those used in the PIT polymerization method.

[0065] In one embodiment, the alcohol-based solvent used as the solvent is 2-8 The reaction yield can be further increased within the above range.

[0066] In the present invention, the solution in which the crosslinked polymer is formed, which is produced by the above-mentioned production method, may be used as a thickener. Also, the solution may be precipitated with a precipitating agent to finally produce a solid thickener such as a powder. In this case, a non-solvent precipitating agent may be used, and in particular, acetone may be used.

[0067] The present invention also provides a thickener produced by the above-mentioned method for producing a thickener.

[0068] FIG. 1 is an illustrative diagram of a method for producing a polymeric thickener according to the present invention (steps 1-1 to 1-3).

[0069] The thickener according to the present invention may be in the form of a spherical thickener produced by the method as shown in FIG.

[0070] The thickener according to the present invention may be in the form of a spherical thickener produced by the method as shown in FIG.

[0071] The thickener according to the present invention has the form of spherical fine particles, swells in water, ethanol or a water-ethanol mixed solution, and can provide a highly viscous solution that is visually uniform in appearance.

[0072] The thickener produced according to the present invention may have an average particle size of 10 to 300 μm.

[0073] The thickener produced in the present invention may have a viscosity of 500 to 150,000 cPs, or 5,000 to 100,000 cPs at 25° C. in a 1% (w / v) aqueous dispersion.

[0074] The present invention will be described in more detail with reference to the following examples and comparative examples. These examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0075] [Example] Comparative Example 1 Aqueous phase: 17 g of acrylamidomethylpropanesulfonic acid and 0.5 g of trimethylolpropane ethoxylate triacrylate were dissolved in 63 g of distilled water, and the solution was neutralized to pH 7-9 with ammonia water.

[0076] Oil phase: 10 g each of polyoxyethylene(3) oleyl ether and polyoxyethylene(6) oleyl ether were added to 80 g of heptane and mixed thoroughly.

[0077] The aqueous phase and the oil phase were added to a reactor and heated to 70°C, after which 0.1 g of the initiator 4,4'-azobis(4-cyanovaleric acid) was added and reacted for 3 hours, and the thickener was precipitated with acetone and dried to obtain the thickener.

[0078] Comparative Example 2 Aqueous phase: 17 g of acrylamidomethylpropanesulfonic acid and 0.5 g of trimethylolpropane ethoxylate triacrylate were dissolved in 63 g of distilled water, and the solution was neutralized to pH 7-9 with ammonia water.

[0079] Oil phase: A certain amount of silicon methacrylate (molecular weight: 5,000) was added to 80 g of heptane and mixed thoroughly.

[0080] The aqueous phase and the oil phase were added to a reactor and heated to 70°C, after which 0.1 g of the initiator 4,4'-azobis(4-cyanovaleric acid) was added and reacted for 3 hours, and the thickener was precipitated with acetone and dried to obtain the thickener.

[0081] In this case, emulsion polymerization using an emulsifier appears to be necessary because the reaction carried out without an emulsifier did not result in a homogeneous reaction and formed a gel that was difficult to use for testing.

[0082] Examples 1 to 3. Aqueous phase: 17 g of acrylamidomethylpropanesulfonic acid and 0.5 g of trimethylolpropane ethoxylate triacrylate were dissolved in 63 g of distilled water, and the solution was neutralized to pH 7-9 with ammonia water.

[0083] Oil phase: A certain amount of silicon methacrylate (molecular weight: 1,000 / 5,000 / 10,000) was added to 80 g of heptane, and 10 g each of polyoxyethylene(3) oleyl ether and polyoxyethylene(6) oleyl ether were added and mixed well.

[0084] The aqueous phase and the oil phase were added to a reactor and heated to 70°C, after which 0.1 g of the initiator 4,4'-azobis(4-cyanovaleric acid) was added and reacted for 3 hours, and the thickener was precipitated with acetone and dried to obtain the thickener.

[0085] The compositions are shown in Table 1 below.

[0086] [Table 1]

[0087] Comparative Example 3. 20g of acrylamidomethylpropanesulfonic acid and 1g of trimethylolpropane ethoxylate triacrylate were added to 100g of t-butanol, and then 6.4g of ammonia water was added and stirred for 30 minutes to completely dissolve.

[0088] After that, the mixture was heated to 70° C., and 0.3 g of the initiator 4,4′-Azobis(4-cyanovaleric acid) was added and reacted for 3 hours. The thickener was then precipitated with ethanol and acetone and dried to obtain the thickener.

[0089] Example 4 20g of acrylamidomethylpropanesulfonic acid and 1g of trimethylolpropane ethoxylate triacrylate were added to 100g of t-butanol, and then 6.4g of ammonia water was added and stirred for 30 minutes to completely dissolve. Next, a certain amount of silicon methacrylate (molecular weight: 5,000) was added and mixed well.

[0090] After that, the mixture was heated to 70° C., and 0.3 g of the initiator 4,4′-Azobis(4-cyanovaleric acid) was added and reacted for 3 hours. The thickener was then precipitated with ethanol and acetone and dried to obtain the thickener.

[0091] The compositions are shown in Table 2 below (unit: g).

[0092] [Table 2]

[0093] Experimental example 1. Comparison of moisture retention (Figure 3) 1 g of each thickener prepared according to the composition of Comparative Examples 1 and 3 and Examples 1 to 4 was dissolved in 99 g of distilled water. Then, 10 g of the polymer solution was transferred to a Petri dish at 55°C and placed in an oven. The weight of the sample was measured at each time to confirm the amount of water evaporation. The results are shown in Figure 3.

[0094] As a result, as shown in Figure 3, the thickeners of Examples 1 to 4 had a significantly longer water retention time than those of Comparative Examples 1 and 3. This means that when silicone is coated, water evaporation is suppressed in the core part of the polymer that contains water, increasing the moisturizing power.

[0095] Experimental example 2. Comparison of color transfer when applied to color cosmetics First, the color cosmetic formulations shown in Table 3 below were prepared.

[0096] The raw materials for the oil phase were first mixed and dissolved by heating to 80°C. During this time, the water phase was added and dissolved, and then the water phase was added to the oil phase and homogenized at 5000 rpm for 10 minutes to prepare the dosage form.

[0097] The prepared formulation was dropped on the bottom of a marble in 30μl portions, spread thinly to a thickness of 25μm, and then dried for 4 hours. 10μl of artificial sebum was dropped on the dried formulation and left at room temperature for 10 minutes, then covered with artificial leather and subjected to 10 reciprocating pressures with a 200g weight. The artificial leather was then peeled off, and the amount of color cosmetics on the leather was visually compared. The results are shown in Figure 4.

[0098] [Table 3]

[0099] As shown in Figure 4, it was confirmed that the higher the molecular weight of the silicone methacrylate used in the synthesis of the polymer, the less color transfer of the color cosmetics. When no polymer was used, the color cosmetics had almost no sebum resistance, and even in the case of polymers not coated with silicone methacrylate, the color transfer of the color cosmetics was at a high level. This is believed to be because the silicone coated on the surface of the spherical polymer is set in the formulation, and the polymers adhere to each other, forming a film that provides sebum resistance and water resistance.

[0100] Experimental Example 3. Comparison of stickiness when applied to color cosmetics 10μl of each color cosmetic from Experimental Example 2 was dropped onto artificial leather and spread over an area of ​​2x2(cm), after which the stickiness was measured as a function of drying time. A cylindrical applicator was used as the Texture Analyzer equipment, and the measurement parameters were set to a measurement speed of 1mm / s and a measurement force of 1.0g, and the stickiness was calculated as the negative energy at the time when the applicator first touched the dried formulation. The results are shown in Table 4 below.

[0101] [Table 4]

[0102] As shown in Table 4, when a general water-dispersible polymer was used, stickiness was very strong, but when silicone methacrylate was used, stickiness was reduced. This is because when a water-dispersible polymer is used to solve the dryness of a color product, the dryness is reduced but stickiness increases, so in order to reduce stickiness while maintaining a moist feeling, a spherical polymer coated with silicone methacrylate can be used.

[0103] Experimental Example 4. Comparison of stickiness when applied to sunscreen cosmetics First, a sunscreen cosmetic formulation was prepared as shown in Table 5 below.

[0104] The raw materials for the oil phase were first mixed and dissolved at 80°C. The water phase was added and dissolved during this time, and then the water phase was added to the oil phase and homogenized at 4000 rpm for 10 minutes to produce the dosage form.

[0105] After dropping 3μl of sunscreen (sun cream) onto artificial leather, the stickiness was measured according to the number of times the applicator touched it. A ball-shaped applicator was used as the Texture Analyzer equipment, and the measurement parameters were set to a measurement speed of 1mm / s and a measurement force of 1.0g, and the measurement was repeated 200 times to calculate the stickiness as the negative energy at the time the applicator touched the dosage form. The results are shown in Figure 5.

[0106] [Table 5]

[0107] As shown in Figure 5, when a general polymer was used, the stickiness was very strong, but when silicone methacrylate was used, the stickiness was reduced. This can be solved by using spherical polymers coated with silicone methacrylate to reduce stickiness while maintaining a moist feeling in UV protection products, just like in color products.

[0108] Experimental Example 5. Comparison of UV blocking performance durability when applied to sunscreen cosmetics 33.5μg of sun cream from Experimental Example 4 was thinly spread on a 5x5cm PMMA plate (Helioplate, Helioscreen, France) for measuring sun protection factor. After 15 minutes, the initial sun protection factor (SPF) was measured using an in vitro measuring device, and after 4 hours, 10μg of artificial sebum was dropped and spread on the PMMA plate on which the sun cream was applied, and the SPF value was measured again after 10 minutes to confirm the change in SPF. The results are shown in Table 6 below.

[0109] [Table 6]

[0110] As shown in the above results, when a silicone methacrylate-coated spherical thickener is used, the SPF reduction rate is less than that of sun creams made using general polymers. As with Experimental Example 2, this shows that the sebum resistance of color cosmetics can be applied to sunscreen cosmetics as is, improving the durability of UV blocking performance.

[0111] Experimental Example 6: Actual use test for stickiness and moisture sensation when applied to a lotion formulation First, a lotion formulation for keratinocyte care was prepared as shown in Table 7 below.

[0112] Twenty women aged 25 to 50 years old applied the lotion formulation to their faces once a day for three days. After application, they were asked to complete a questionnaire about the sensation of use. The sensation of use was evaluated according to the following criteria: ◎: 16 or more out of 20 subjects answered that it was not sticky or had a high sense of moisture, ○: 12 to 15 out of 20 subjects answered that it was not sticky or had a high sense of moisture, △: 8 to 11 out of 20 subjects answered that it was not sticky or had a high sense of moisture. The results are shown in Table 7 below.

[0113] [Table 7]

[0114] As can be seen from the results shown in Table 7, keratin management ingredients in formulations for keratin management are highly sticky, but by using the polymer provided by the present invention, stickiness is reduced and the feeling of moisture is increased.

Claims

1. An amphiphilic thickener comprising a crosslinked polymer obtained by polymerizing a water-soluble monomer and a crosslinkable monomer represented by Chemical Formula 1 with a silicone-containing monomer represented by Chemical Formula 2 below. [Chemical formula 1] 【Chemistry 1】 In the above Chemical Formula 1, R 1 is -H, -CH 3 , -CH 2 CH 3 Or - (CH 2 ) m CH 3 where m=1 to 3; R 2 is -OX,NH 2 Or -NH-R 3 -SO 3 Y, R 3 is -(CH 2 ) -, -(CH 2 ) 2 -, -(CH 2 ) 3 -, -(CH 2 ) 4 -, -(CH 2 ) 2 (CH3) 2 - or - (CH 2 ) 3 CH 3 - and X and Y are H + , Na + , Li + , K + or NH 3 + and X and Y may be the same as each other. [Chemical formula 2] 【Chemistry 2】 In the above Chemical Formula 2, m is an integer from 1 to 5, n is an integer from 10 to 5000, R 1 is hydrogen or C 1-3 is an alkyl group, R 2 is a hydroxy group, C 1-3 It is an alkyl group or a vinyl group.

2. The amphiphilic thickener according to claim 1, wherein the water-soluble monomer represented by Chemical Formula 1 comprises at least one selected from the group consisting of acrylamidomethylpropanesulfonic acid (AMPS), acrylic acid, acrylamide, and polyethylene glycol acrylate.

3. The amphiphilic thickener according to claim 1 , wherein the water-soluble monomer represented by Chemical Formula 1 is a compound represented by Chemical Formula 1a below: [Chemical formula 1a] 【Chemistry 3】

4. A step of preparing an oil-in-water emulsion composition comprising an aqueous phase including a water-soluble monomer represented by the following formula 1 and a crosslinkable monomer, and an oil phase including a silicone-containing monomer represented by the following formula 2 and a non-polar organic solvent: A step of heating to 60° C. or higher to produce a water-in-oil type reverse emulsion composition; and A method for producing an amphiphilic thickener, comprising the step of adding an initiator to carry out a polymerization reaction to produce a cross-linked polymer. [Chemical formula 1] 【Chemistry 4】 In the above Chemical Formula 1, R 1 is -H, -CH 3 , -CH 2 CH 3 Or - (CH 2 ) m CH 3 where m=1 to 3; R 2 is -OX,NH 2 Or -NH-R 3 -SO 3 Y, R 3 is -(CH 2 ) -, -(CH 2 ) 2 -, -(CH 2 ) 3 -, -(CH 2 ) 4 -, -(CH 2 ) 2 (CH3) 2 - or - (CH 2 ) 3 CH 3 - and X and Y are H + , Na + , Li + , K + or NH 3 + and X and Y may be the same as each other. [Chemical formula 2] 【Chemistry 5】 In the above Chemical Formula 2, m is an integer from 1 to 5, n is an integer from 10 to 5000, R 1 is hydrogen or C 1-3 is an alkyl group, R 2 is a hydroxy group, C 1-3 It is an alkyl group or a vinyl group.

5. Dissolving a water-soluble monomer represented by the following Formula 1, a crosslinkable monomer, and a silicone-containing monomer represented by the following Formula 2 in an alcohol-based solvent: Heating to 60° C. or higher; and A method for producing an amphiphilic thickener, comprising the step of adding an initiator to carry out a polymerization reaction to produce a cross-linked polymer. [Chemical formula 1] 【Chemistry 6】 In the above Chemical Formula 1, R 1 is -H, -CH 3 , -CH 2 CH 3 Or - (CH 2 ) m CH 3 where m=1 to 3; R 2 is -OX,NH 2 Or -NH-R 3 -SO 3 Y, R 3 is -(CH 2 ) -, -(CH 2 ) 2 -, -(CH 2 ) 3 -, -(CH 2 ) 4 -, -(CH 2 ) 2 (CH3) 2 - or - (CH 2 ) 3 CH 3 - and X and Y are H + , Na + , Li + , K + or NH 3 + and X and Y may be the same as each other. 【Chemistry 7】 In the above Chemical Formula 2, m is an integer from 1 to 5, n is an integer from 10 to 5000, R 1 is hydrogen or C 1-3 is an alkyl group, R 2 is a hydroxy group, C 1-3 It is an alkyl group or a vinyl group.

6. The method for producing an amphiphilic thickener according to claim 4 or claim 5, wherein the water-soluble monomer represented by Chemical Formula 1 includes at least one selected from the group consisting of acrylamidomethylpropanesulfonic acid (AMPS), acrylic acid, acrylamide, and polyethylene glycol acrylate.

7. The method for producing an amphiphilic thickener according to claim 4 or claim 5, wherein the water-soluble monomer represented by Chemical Formula 1 is a compound represented by the following Chemical Formula 1a: [Chemical formula 1a] 【Chemistry 8】

8. The method for producing an amphiphilic thickener according to claim 4 or claim 5, wherein the water-soluble monomer represented by Chemical Formula 1 is contained in an amount of 50 to 95% by weight based on 100% by weight of the total of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2.

9. The method for producing an amphiphilic thickener according to claim 4 or claim 5, wherein the crosslinkable monomer is a compound having two or more acrylate groups, two or more acrylamide groups, or two or more vinyl groups.

10. The non-polar organic solvent is 6-17 A method for producing the amphiphilic thickener of claim 4, which is a hydrocarbon oil.

11. The method for producing an amphiphilic thickener according to claim 4 or 5, wherein the silicone-containing monomer represented by Chemical Formula 2 is contained in an amount of 5 to 50% by weight relative to 100% by weight, which is the total weight of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2.

12. 5. The method of claim 4, wherein the oil phase further comprises at least one surfactant, the total HLB value of the combination of surfactants being between 6 and 14.

13. The method for producing an amphiphilic thickener according to claim 12, wherein the surfactants are two types of surfactants, one having an HLB value of 3 to 8 and the other having an HLB value of 8 to 16.

14. The method for producing an amphiphilic thickener according to claim 4 or 5, wherein the reaction initiator is at least one selected from the group consisting of peroxides and azo compounds.

15. The method for producing an amphiphilic thickener according to claim 4 or 5, wherein the polymerization reaction is carried out at 60° C. or higher for 2 to 6 hours.

16. The alcohols are 2-8 The method for producing the amphiphilic thickener according to claim 5, which is an alcohol.

17. A method for preparing an amphiphilic thickener according to claim 4 or 5, further comprising a step of precipitating with a precipitating agent to obtain the thickener in solid form.

Citation Information

Patent Citations

  • Thickener with fine grain structure with improved usability

    KR102531603B1